2017
DOI: 10.3164/jcbn.16-48
|View full text |Cite
|
Sign up to set email alerts
|

Black soybean seed coat polyphenols prevent AAPH-induced oxidative DNA-damage in HepG2 cells

Abstract: Black soybean seed coat extract (BE), which contains abundant polyphenols such as procyanidins, cyanidin 3-glucoside, (+)-catechin, and (−)­epicatechin, has been reported on health beneficial functions such as antioxidant activity, anti-inflammatory, anti-obesity, and anti-diabetic activities. In this study, we investigated that prevention of BE and its polyphenols on 2,2'-azobis(2-methylpropionamide) dihydrochloride (AAPH)-induced oxidative DNA damage, and found that these polyphenols inhibited AAPH-induced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 37 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…23 Furthermore, BSB active compound suppresses oxidative damage in DNA by neutralizing free radical in cytosol and nucleus. 24 In addition, PSP rich-anthocyanins contents prevent free radical of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and superoxide radical. 25 The combination of BSB and PSP reduce MDA concentration in DM rats.…”
Section: Discussionmentioning
confidence: 99%
“…23 Furthermore, BSB active compound suppresses oxidative damage in DNA by neutralizing free radical in cytosol and nucleus. 24 In addition, PSP rich-anthocyanins contents prevent free radical of 2,2-diphenyl-1-picrylhydrazyl (DPPH) and superoxide radical. 25 The combination of BSB and PSP reduce MDA concentration in DM rats.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed method is written in the later section ( Section 2.8 , Extraction and Quantification of Polyphenols.) For the antioxidant activity, the 2, 2′-azobis (2-amidinopropane) dihydrochloride (AAPH) radical absorbance capacity of black soybean and placebo cookies was measured [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, isoflavones are major polyphenols in the grain of black soybean, as they are in the yellow one. Previous studies reported that polyphenols in the black soybean had various beneficial physiological functions, such as antioxidant in HepG2 cells [ 9 ], anti-obesity, and anti-diabetic activities in C57BL/6 mice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…AAPH can react with oxygen in the air to produce peroxy radicals (ROO_) at a steady rate. ROO_ can capture the hydrogen atom supplied by the C-4′ atom in DNA, which could result in the DNA molecule unwinding and generating a variety of carbonyl-containing small molecular substances [23,28]. ese substances can react with TBA to produce thiobarbituric acid reactive species (TBARS, λ max � 535 nm) under acidic conditions.…”
Section: Protective Effects Of 5a-5dmentioning
confidence: 99%